2018
DOI: 10.1142/s1793042118501002
|View full text |Cite
|
Sign up to set email alerts
|

A note on Diophantine approximation by unlike powers of primes

Abstract: It is proved that if [Formula: see text] are nonzero real numbers, not all of the same sign and [Formula: see text] is irrational, then for given real numbers [Formula: see text] and [Formula: see text], [Formula: see text], the inequality [Formula: see text] has infinitely many solutions in prime variables [Formula: see text]. This result constitutes an improvement upon that of Liu for the range [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…e proof of (19) is quite similar to that given in Section 3 in [20]. For completeness of exposition, we briefly present the proof procedure below.…”
Section: The Major Arcmentioning
confidence: 85%
See 1 more Smart Citation
“…e proof of (19) is quite similar to that given in Section 3 in [20]. For completeness of exposition, we briefly present the proof procedure below.…”
Section: The Major Arcmentioning
confidence: 85%
“…Subsequently, Liu [19] obtained 0 < σ(5) < 5/288. In [20], the first author and Qu showed that 0 < σ(5) < 5/252 is acceptable. Very recently, this result was improved by Zhu [21], who obtained 0 < σ(5) < 1/48.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we give a low bound for the integral on the major arc M. First, we consider the standard major arc M * = {α : |α| ≤ X − + / −ε }. Using the idea due to Harman [7], we get the following lemma (one can also see section 3 of Mu and Qu [16]). One may improve the standard major arc to {α : |α| ≤ X − + / −ε } by using some ideas due to Languasco and Zaccagnini [10] (one can also see [5]).…”
Section: The Major Arcmentioning
confidence: 99%
“…Later, Mu [15], Liu [13], Mu and Qu [16] replaced in (1.1) with / , / and / respectively. In this paper, under some extra conditions of λ j , we get the following result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation